Pengaturan Lembaga Jaminan Fidusia Di Indonesia Perspektif Undang-Undang No.42 Tahun 1999 Tentang Jaminan Fidusia - M. Yadi Harahap (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2017)
The arrangement of collateral in accordance with the provisions of applicable law in Indonesia comprises material collateral consisting of movable and immovable property.One of the properties of material security has inherent properties and follows objects that are the object of guarantee wherever located (droit de suite) means the collateral of material is an additional collateral (accessoir) which always follow the basic guarantee.For The collateral of material in Indonesia is fiduciary collateral regulated through Act No. 42 of 1999 on Fiduciary Guarantee.The principal issue in this research is how actually the construction, arrangement and imposition of fiduciary collateral according to the provisions of the regulations in force in Indonesia. To answer the research question, the method used by normative juridical approach with statute approach is Act No. 42 of 1999 on Fiduciary Guarantee, It is possible to find a systematic and comprehensive answer.   Keywords: collateral, fiduciary,UU No. 42 of 1999 on fiduciary collateral, regulation